MPC-based Anesthesiologists Imitating Control of Propofol and Remifentanil during Anesthesia Maintenance - Raymond, Maxim; Moussa, Kaouther; Fiacchini, Mirko; Lauber, Jimmy (International Conference on System Theory, Control and Computing, 2025)
This paper suggests a new formulation of a Model Predictive Control (MPC) strategy, allowing to design propofol and remifentanil infusion profiles in order to control the Bispectal Index (BIS). This new formulation, based on a range cost, allows to reduce the sensitivity of the control profiles with respect to the BIS measurement noise. Furthermore, it allows to better represent the anesthesiologists behavior in practice, who usually do not over-react to small changes in the measured health indicators. The paper assesses numerically this formulation, by comparing its performance, in an uncertain setting, to standard set-point tracking based MPC strategies.